Re-description of three little known species of Palaearctic Chrysoesthia Hübner, [1825], with description of the hitherto unknown female of Chrysoesthia falkovitshi Lvovsky & Piskunov, 1989 (Lepidoptera: Gelechiidae) - Oleksiy V. Bidzilya (SHILAP)
Additions to original descriptions are provided for three little-known species - Chrysoesthia falkovitshi Lvovsky & Piskunov, 1989, C. mironovi Bidzilya, 2001 and C. tuvella Bidzilya, 2005. The colour photographs of adults and ventral view of the male genitalia are given for all three species for the first time, and their diagnostic characters are discussed. The hitherto unknown female genitalia of C. falkovitshi are described. The diagnosis of the genus and its differences from closely related Metanarsia Staudinger, 1871 are briefly discussed